The Effect of Age, Gender and Comorbidities Upon SARS-CoV-2 Spike Antibody Induction After Two Doses of Sinopharm Vaccine and the Effect of a Pfizer/BioNtech Booster Vaccine - Farid, Eman; Herrera-Uribe, Juber; Stevenson, Nigel J. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus (SARS-CoV)-2 emerged in China in 2019 and has since travelled the world infecting millions. SARS-CoV-2 causes Corona Virus Disease (COVID-19), that has to date taken over 4 million lives. The Kingdom of Bahrain’s vaccine roll-out has consisted of Sinopharm’s BBIBP-CorV (Sinopharm) and Pfizer/BioNtech’s BNT162b2 (Pfizer/BioNtech). Testing for SARS-CoV-2 anti-Spike (S) antibodies is a useful technique in estimating an individual’s immune protection against the infection. In this study we evaluated S antibody levels by electro-chemiluminescence immunoassay in 379 individuals double vaccinated with Sinopharm and 15 of whom were given a booster with the Pfizer/BioNtech vaccine. Among our double vaccinated cohort, we found a spectrum of S antibody levels. Indeed, we found that a significant proportion of individuals with low S antibody levels had clinical conditions, which were mainly immune-related disorders. Furthermore, a significant proportion of individuals with low S antibody levels were above 50 years of age. Finally, we observed a significant increase in S antibody levels after the Pfizer/BioNtech booster was administered. These findings reveal that while a large proportion of Sinopharm vaccinated individuals did not develop high levels of antibodies against the S protein, a booster dose of the Pfizer/BioNtech vaccine significantly enhances S antibody levels, revealing this “triple dose” vaccination strategy as a useful method of ensuring protective immunity against SARS-CoV-2.